Can Deliberative Participatory Fora Cure Representation Gaps in France and Germany? - Agnes Blome; Miriam Hartlapp (Politische Vierteljahresschrift, 2023)
The French and the German national parliaments are dominated by highly educated, older, and mostly male politicians. There are growing calls for a~more balanced political representation of different social groups. This paper seeks to inform this debate by conceptualizing and measuring representation gaps for women, people of immigrant origin, the working class, and younger age groups in France and Germany and by assessing the potential of deliberative participatory fora to ameliorate underrepresentation. Based on theories of deliberative and participatory democracy, it suggests three criteria these fora must fulfill to potentially balance underrepresentation (descriptive representation in composition, deliberative quality, and coupling to politics) and explores them empirically in four recent cases of deliberative participatory fora: the Grand Débat National and the Convention Citoyenne pour le Climat in France and the Bürgerrat Deutschlands Rolle in der Welt and the Bürgerrat Klima in Germany. We show that significant representation gaps exist for all groups studied. They have been narrowing for women and people of immigrant origin and remain most pronounced for class. Regarding institutional features, our cases fare relatively well in terms of balanced composition and deliberative quality, but the potential to balance representation gaps is seriously limited by a~lack of coupling to the political system.
Keywords: 320; Descriptive representation; Social groups; Political inequality; Democracy; Citizen assemblies; Deskriptive Repräsentation; Soziale Gruppen; Politische Ungleichheit; Demokratie; Bürgerräte